The psychological impact of symptoms related to esophagogastric cancer resection presenting in primary care: A national linked database study. Issue 2 (February 2017) - Bouras, G.; Markar, S.R.; Burns, E.M.; Huddy, J.R.; Bottle, A.; Athanasiou, T.; Darzi, A.; Hanna, G.B.
Abstract: Background: The objective was to evaluate incidence, risk factors and impact of postoperative symptoms following esophagogastric cancer resection in primary care. Methods: Patients undergoing esophagogastrectomy for cancer from 1998 to 2010 with linked records in Clinical Practice Research Datalink, Hospital Episodes Statistics and Office of National Statistics databases were studied. The recording of codes for reflux, dysphagia, dyspepsia, nausea, vomiting, dumping, diarrhea, steatorrhea, appetite loss, weight loss, pain and fatigue were identified up to 12 months postoperatively. Psychiatric morbidity was also examined and its risk evaluated by logistic regression analysis. Results: Overall, 58.6% (1029/1755) of patients were alive 2 years after surgery. Of these, 41.1% had recorded postoperative symptoms. Reflux, dysphagia, dyspepsia and pain were more frequent following esophagectomy compared with gastrectomy (p < 0.05). Complications (OR = 1.40 95%CI 1.00–1.95) and surgical procedure predicted postoperative symptoms (p < 0.05). When compared with partial gastrectomy, esophagectomy (OR = 2.03 95%CI 1.26–3.27), total gastrectomy (OR = 2.44 95%CI 1.57–3.79) and esophagogastrectomy (OR = 2.66 95%CI 1.85–2.86) were associated with postoperative symptoms (p < 0.05). The majority of patients with postoperative psychiatric morbidity had depression or anxiety (98%). Predictors of postoperative depression/anxiety included younger age (OR = 0.97 95%CI 0.96–0.99), complications (OR = 2.40 95%CI 1.51–3.83), psychiatric history (OR = 6.73 95%CI 4.25–10.64) and postoperative symptoms (OR = 1.78 95%CI 1.17–2.71). Conclusions: Over 40% of patients had symptoms related to esophagogastric cancer resection recorded in primary care, and were associated with an increase in postoperative depression and anxiety.